In Vitro Morphogenesis Responses of Various Explant in Physalis angulata L. - Mastuti, Retno; Munawarti, Aminatun (Graduate School, Universitas Brawijaya, 2017)
The objective of this research was to identify morphogenesis responses of in vivo and in vitro-derived explant of Physalis angulata L. Explants were cultured on MS medium containing 3% sucrose solidified with 1.3% agar supplemented with combination of 6-benzylaminopurine (BAP), indole acetic acids (IAA), naphthalene acetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D). All explant types have morphogenesis ability. Capability for shoot regeneration was observed in high number of shoot tip (96.1%) and nodes explants (75.2%). Callus formation was dominantly produced by in vitro leaf explants. In vivo leaf had low responses for shoot/root regeneration and callus formation. These results provided an alternative choice of the explant suitable for either plant regeneration or callus formation.Keywords: callus, cotyledonary nodes, explant types, shoot regeneration.